2012
DOI: 10.1097/jto.0b013e31825f22ee
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Intermittent Sunitinib Malate as Second-Line Therapy in Progressive Malignant Pleural Mesothelioma

Abstract: Sunitinib has activity in a subset of patients with pretreated MPM. Consideration should be given to different treatment schedules and examination of other biomarkers for further study of sunitinib in MPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 43 publications
1
50
0
1
Order By: Relevance
“…Malignant mesothelioma is an uncommon cancer (2) with limited therapeutic options (8,(10)(11)(12) and poor clinical outcomes (4,5). Thus, we investigated the genomic landscape of this tumor by targeted NGS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant mesothelioma is an uncommon cancer (2) with limited therapeutic options (8,(10)(11)(12) and poor clinical outcomes (4,5). Thus, we investigated the genomic landscape of this tumor by targeted NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular singletons as the norm are commonly reported in other cancers as well (44)(45)(46)(47)(48). Considering that effective therapies for mesothelioma are lacking (8)(9)(10)(11)(12), clinical trials for mesothelioma that incorporate molecular profiling for patient selection and appropriately customized therapy are warranted (49).…”
Section: Discussionmentioning
confidence: 99%
“…Pazopanib was well tolerated and the primary endpoint PFS rate at 6 months was 47% [Garland et al 2011] [ClinicalTrials.gov identifier: NCT00459862]. Sunitinib, a similar multitargeted TKI, demonstrated variable results in patients with pretreated disease and has also not moved forward into further trials [Laurie et al 2011;Nowak et al 2012].…”
Section: Inducing Angiogenesismentioning
confidence: 99%
“…This was the reason to proceed with a larger randomized phase II trials testing cediranib in combination with pemetrexed and cisplatin. A second phase II study of sunitinib as second-line therapy reported modest activity in progressing patients, but was unable to identify any serum biomarkers of response in angiogenesis pathways [45]. A large randomized phase III study examined the oral antiangiogenic drug thalidomide in a switch maintenance setting.…”
Section: Vascular Targeted Drugsmentioning
confidence: 99%